THE STUDENT DIFFICULTIES IN THE IMPLEMENTATION OF CAMBRIDGE CURRICULUM AT AL-AZHAR JUNIOR HIGH SCHOOL - Trimadona, Eliza; Andriani, Reni; Dwiputri Ferdi, Sherly (JR-ELT (Journal of Research in English Language Teaching), 2020)
The primary goal of this research is to determine what processes and materials are required to implement the Cambridge curriculum at Al-Azhar Junior High School Jambi. The second objective of the research is to identify the factors and challenges that students encounter during the application and learning of English using the Cambridge curriculum. This investigation employs a qualitative methodology. The subjects of this investigation were the Al-Azhar Junior High School Jambi principal, English teacher, and eighth grade students. Interviews, observations, and documentation were used to collect the research data. Based on the findings and discussions encountered by the researcher during the application of the Cambridge curriculum at AlAzhar Junior High School Jambi via multiple processes, including the planning, implementation, and evaluation processes, as well as the implementation of the curriculum at AlAzhar Junior High School Jambi by the education unit and teachers. At ALAzhar Junior High School Jambi, certain students encountered difficulties with the Cambridge curriculum's learning process during its implementation. Lack of vocabulary comprehension, lack of motivation to learn, pronunciation errors, and anxiety during the learning process are some of the challenges faced by students. It has been going well for the implementation of the Cambridge curriculum at Al-Azhar Junior High School, despite the fact that there are still some impeding factors. However, this is not a major issue, as the implementation of the Cambridge curriculum at Al-Azhar Junior High School Jambi has been operating as optimally as possible.